Prognostic Significance of Lineage Diversity in Bladder Cancer Revealed by Single-Cell Sequencing - Yu, Lu; Hu, Rixin; Peng, Guoyu; Ding, Qiuxia; Tao, Tao; Wu, Song (Frontiers in Genetics, 2022)
Bladder cancer is the most common malignant tumor of urinary system. We investigated clinical implications of cell lineages in bladder cancer by integrating single-cell and bulk transcriptome data. By investigating single-cell transcriptional profiles of 12,424 cells from normal bladder, 11 cell types and 5 types of epithelial sub-population were identified. Based on signature of cell types identified in single-cell profiles, deconvolution analysis was employed to estimate cell types and epithelial lineages in bulk RNA sequencing bladder cancer cohort. Cancer subtypes with clinical implications were further identified based on heterogeneity of epithelial lineage across patients. This study suggests that EMT-like subtype is robustly correlated with poor prognosis and umbrella subtype is a positive factor for the patient's survival. Our research has a high potential to accurate prognostic and therapeutic stratification of bladder cancer.